CyberMaster: An Expert System to Guide the Development of Cybersecurity Curricula - Hodhod, Rania; Khan, Shamim; Wang, Shuangbao (International Journal of Online and Biomedical Engineering (iJOE), 2019)
The growing number of reported cyber-attacks pose a difficult challenge to individuals, governments and organizations. Adequate protection of information systems urgently requires a cybersecurity-educated workforce trained using a curriculum that covers the essential skills required for different cybersecurity work roles. The goal of the CyberMaster expert system is to assist inexperienced instructors with cybersecurity course design. It is an intelligent system that uses visual feedback to guide the user through the design process. Initial test executions show the promise of such a system in addressing the enormous shortage of cybersecurity experts currently available for designing courses and training programs.